The Relationship Between Access to Information Services and Youth Involvement in Agribusiness Value Chains in Kakamega County, Kenya. - Rogito, Jeremiah; Makhanu, Everlyne (Advances in Social Sciences Research Journal, 2022)
Agribusiness offers huge employment potential considering its wider labour absorptive capacity. However, youth involvement in agribusiness in Kakamega County, Kenya is low. The study aimed at assessing the relationship between access to information services and youth involvement in agribusiness value chains. Stratified and simple random sampling was adopted to select 240 respondents. Data collected was analyzed to generate frequencies, percentages and correlation. It was established that there is a strong correlation between access to information and youth involvement in agricultural value chains. Lack of or inadequate access to information services is a key constrain to agricultural productivity in Kakamega county as it affects all aspects of the value chain except consumption. County governments and the Ministry of Agriculture will use these findings to design appropriate agricultural messaging strategies. Policymakers and Donor agencies using these findings will be able to formulate policies that will enhance youth involvement in the Value Chain by knowing what segments of the value chain to focus on youth intervention strategies.